Self-reported removal and expulsion of the dapivirine vaginal ring: qualitative reports from female ring users and their male partners in the Ring Study (IPM 027) - Cecilia Milford; Hariska Ramlal; Rorisang Mofokeng; Letitia Rambally Greener; Annaléne Nel; Jennifer Smit; Mariëtte Malherbe (BMC, 2024)
Abstract Background/aims The dapivirine vaginal ring is a self-administered, women-initiated, discreet, long-acting HIV-1 prevention option for women. It was found to be safe and effective in healthy HIV-negative women who adhered to product use instructions, and has been approved for use in women aged 18 and older in some African countries. A qualitative study was conducted to explore participants' and their male partners' discussions on accidental/purposeful vaginal ring removals during The Ring Study (IPM 027 clinical trial). Methods Data were collected via in-depth interviews and focus group discussions with female trial participants and their male partners, from seven research centres in South Africa and Uganda. Data were thematically analysed using NVivo. Results More participants reported purposeful ring removals than accidental expulsions. Various factors influenced purposeful ring removal - including individual (discomfort during use/sex and to clean it), partner (to show them, because of discomfort during sex, to test if partners could feel it, and concerns of harm), organisational (doctor's request), and socio-cultural (rumours about sickness and infertility). Some described their own ring use removal, others discussed why other participants removed their rings. Conclusions Vaginal ring adherence is critical to improve and support product efficacy. Counselling on vaginal anatomy, vaginal ring insertion and importance of adherence is important to minimise vaginal ring removal. Couples counselling is also important to facilitate support and long-term vaginal ring adherence behaviour. Understanding factors influencing vaginal ring adherence is important for tailoring and targeting messages to support correct and consistent vaginal ring use as it is made available to the public.